The impact of digital marketing on the pilgrim’s experience: A field study - Alhazmi, Basim Saud; Baishin, Masher Hani; Rajkhan, Dana Monzer (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to analyze the impact of digital marketing on the experience of Umrah performers in Saudi Arabia, with a focus on the benefits and challenges associated with utilizing digital marketing tools in the Umrah sector. The study adopted a descriptive-analytical methodology and utilized a questionnaire as the primary data collection tool, which was distributed to a random sample of 200 Umrah performers. The study focused on three main dimensions: the physical environment (transportation, hotels, public facilities), interaction with employees, and complementary services. The findings revealed a statistically significant positive impact of digital marketing on the physical environment and complementary services, whereas no significant impact was observed on employee interaction. Additionally, the results indicated that mobile applications were the most frequently used digital marketing tool, while transportation services were among the most utilized services by Umrah performers through these tools. Based on the findings, the study recommended enhancing investments in the development of mobile applications to improve user experience, improving transportation services provided through digital platforms to better meet customer needs, enhancing the efficiency of interaction between customers and customer service staff, and continuing to provide innovative complementary services that address the needs of Umrah performers, ultimately contributing to a comprehensive improvement in their religious and personal experiences.